Time and Cost Efficiency Analysis of Hotmix Road Rehabilitation: A Case Study in Papring, Kalipuro District - Prasetyo, Novan Dwi; Sunarko; Prasetyo, Yohanes Pracoyo Widi; Pratama, Ananta Kusuma Yoga (Journal of Development Research, 2025)
Efficient project delivery is a critical requirement for rural road rehabilitation programs, yet empirical evaluations of implementation efficiency remain limited. This study analyzes the time and estimated cost efficiency of the Papring Hotmix Road Rehabilitation Project in Kalipuro District, Banyuwangi, using a descriptive quantitative case study approach based on weekly and monthly project documentation. Project performance was measured by comparing baseline planning with field realization, supported by calculations of time efficiency, deviation analysis, and cost implication estimation derived from work-weight distribution. The project was completed in 55 days, significantly faster than the 120-day planned duration, resulting in a time efficiency of 54.17% and a maximum positive deviation of +76.32% at completion. Major work components: AC-WC (65.616%), AC-BC (18.249%), and aggregate base layer (12.436%), were executed intensively between Weeks 4 and 7, enabling a shortened execution period that suggests potential savings in indirect project costs such as overhead, labor, and field operations. Acceleration was driven by effective technical scheduling, early resource mobilization, optimized labor deployment, and strong contractor–consultant coordination. The findings highlight the importance of structured progress evaluation for improving scheduling and cost control in rural road rehabilitation projects. Future work should incorporate financial realization data and risk-productivity modelling to strengthen efficiency assessment in accelerated infrastructure delivery.